Strategi Guru Pendidikan Agama Islam dalam Membentuk Karakter Religius Melalui Pembelajaran Al-Quran Siswa Muslim Thailand - Nova Kharismatul Indah; Imam Mashuri; Rifqi Firdaus (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2026)
This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in shaping religious character through learning the Qur'an in Muslim students at Ban Kolokawe School, Thailand, in the context of minority communities. The research uses a qualitative approach with an intrinsic case study design. Data were collected through interviews, participatory observations, and documentation, and analyzed using interactive models with triangulation techniques to maintain credibility. The results of the study show that teachers' strategies are integrative, including the habit of reading the Qur'an, direct guidance, examples, associating the meaning of verses with daily life, and supervising student behavior. This strategy not only focuses on the cognitive aspect, but also includes affective and practical aspects. Learning the Qur'an has been proven to be able to cultivate religious character such as discipline, love for the Qur'an, good manners, honesty, responsibility, and social concern. The success of character formation is measured through the ability to read and memorize the Qur'an as well as changes in students' behavior in daily life, thus demonstrating a holistic evaluation approach. However, character formation is also influenced by external factors such as family and social environment. This study concludes that contextual and sustainable Qur'an learning strategies play an important role in shaping students' religious character and maintaining Islamic identity in the context of Muslim minorities. Keywords: Islamic Religious Education; Learning the Qur'an; Teacher Strategies; Religious Character; Muslim minority.